Respuesta :
Answer:
x³ + 4x² - 3x - 2
Step-by-step explanation:
Each term in the second factor is multiplied by each term in the first factor
(x - 1)(x² + 5x + 2)
= x(x² + 5x + 2) - 1(x² + 5x + 2) ← distribute both parenthesis
= x³ + 5x² + 2x - x² - 5x - 2 ← collect like terms
= x³ + 4x² - 3x - 2
Answer:
[tex] x^3 + 4x^2 - 3x - 2 [/tex]
Step-by-step explanation:
You need to multiply a binomial by a trinomial.
[tex] (x-1)(x^2+5x+2) = [/tex]
Multiply each term of the binomial by each term of the trinomial.
[tex] = x^3 + 5x^2 + 2x - x^2 - 5x - 2 [/tex]
Now, combine like terms and write answer in descending order of exponent.
[tex] = x^3 + 4x^2 - 3x - 2 [/tex]